Modern democracy in creating ethical leadership in the Muslim world: a perspective of Tawhidic paradigm - Nabi, Ashiqun; Mhd. Sarif, Suhaimi (World Business Institute, 2015)
This paper postulates critical explanation from Tawhidic paradigm on the relationship between modern democracy and ethical leadership in the Muslim world. This paper examines whether the pragmatic democracy creates ethical leadership in the governments of the Muslim world or not. The study conducted a survey with the sample of 25 postgraduate students of Graduate School of Management (GSM), International Islamic University Malaysia in 2011. The selection of the respondents was based on convenient random sampling from 200 postgraduate students from various countries. The preliminary results of the survey indicated that the Western democracy has insignificant role in creating ethical leadership from Tawhidic paradigm – the element of Unity of God. Furthermore the this research found that, lack of accountability and transparency lead to the Muslim world to be worst off from the Modern democracy which impedes to create ethical leadership.